Pengaruh Model Pembelajaran Contexstual Teaching And Learning (Ctl) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PKN Kelas III di SD Negeri 124385 Jl. Sawi - Mei Putri Sihombing; Esti Sirait; Sukardo Sitohang (Jurnal Pendidikan Dasar Islam, 2024)
This research aims to determine the influence of the Contextual Teaching and Learning (Ctl) learning model on student learning outcomes in Civics Class III subjects at SD Negeri 124385 Jl. Mustard. The type of research that suits the title of this research is quantitative. There are three types of Pre-Experimental research, but the researcher used One Group Pretest-Posttest Design research. One Group Pretest-Posttest is a type of research that compares conditions before treatment and conditions after treatment. Based on the results of the research and discussions that have been carried out, namely to determine the influence of Contextual Teaching and Learning (CTL) on the social studies learning outcomes of class V students at SD Negeri 124385 Jl. Sawi, it can be concluded as follows: That the student learning outcomes before being given treatment were mostly still not achieved the KKM, that is, students obtained a score above the KKM of 39.28% (12 students) the remaining 60.72% (18 students) had a score still below the KKM. However, after being given treatment, student learning outcomes increased, namely students who obtained above the KKM amounted to 100% (30 students). Based on the results of the hypothesis test that has been carried out, it is found that t = 18.115 while t table = 2.045. So tcount>ttable so that the hypothesis in this research is accepted and successful. So Ho is rejected and Ha is accepted. This shows that there are differences between student learning outcomes using the Contextual Teaching And Learning (CTL) model.